A case of a positive coccidioides stool culture in an immunocompetent patient with disseminated coccidioidomycosis. (2017) - Alfreijat, Majd; Wilhelmi, Brian
Abstract: Coccidioidomycosis (CM) is an infection caused by the coccidioides fungus. The spectrum of the disease ranges from a mild upper respiratory illness to severe disseminated infection that could affects the bones, joints, skin, central nervous system, and the gastrointestinal tract. Previous reports of a positive stool culture in the setting of disseminated CM are extremely rare. Herein, we describe a case of a 43-year-old immunocompetent patient with disseminated CM and evidence of positive coccidioides stool culture.